Method of providing low gloss coating
Through the aqueous radiation curable coating composition and specific ultraviolet irradiation steps, the problem of high gloss after drying of the water-based vinyl polymer coating composition in the prior art is solved, and a low-gloss coating without matting agent is achieved, and the resistance of the coating is improved.
Patent Information
- Application Number
- CN202380061079.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-22
- Publication Date
- 2025-04-01
AI Technical Summary
Existing aqueous vinyl polymer coating compositions usually obtain a glossy surface after drying, and the use of matting agents results in reduced coating performance and reduced tolerance.
Low gloss coatings are obtained without the use of matting agents by using an aqueous radiation-curable coating composition using a sequential UV irradiation step, including excimer radiation at a wavelength of ≤220 nm and ultraviolet light or electron beam irradiation at a wavelength of ≥300 nm.
A low gloss coating is achieved without matting agent, improving the coffee and water resistance of the coating, and achieving it while essentially free of radiation-curable ethylenically unsaturated bonds in the vinyl polymer system.
Smart Images

Figure BDA0005279436040000191 
Figure BDA0005279436040000211 
Figure BDA0005279436040000221
Abstract
Description
[0001] The present invention relates to the field of waterborne vinyl polymer coating compositions for producing coatings having a high matte (ie low gloss) finish.
[0002] Aqueous vinyl polymer (especially acrylic copolymer) coating compositions are widely used in the coating industry. However, a glossy surface is usually obtained after the aqueous coating composition has dried. "Low gloss" surfaces give products a highly sought-after aesthetic effect, especially in the wooden furniture, flooring and wall covering industries, because they can create a very natural appearance, which helps to emphasize the materiality of the product more. Currently, the creation of a matt surface usually involves the use of coating products whose formulations contain matting agents made of organic and / or inorganic substances, which can act on the degree of reflection of light by positioning themselves on the coating surface and / or floating on the coating surface to give the observer the visual perception of a low gloss surface. However, the use of matting agents leads to a deterioration of the surface properties of the coating because they do not participate in the polymerization process. In addition, matting agents tend to migrate to the coating surface after application, so that the matting agents may be lost during mechanical deformation, such as caused by scratching, so that the glossiness is increased.
[0003] The use of matting agents also severely reduces the resistance to typical household chemicals such as coffee. The long-term action of these household chemicals leads to at least a degradation of the coating and can even lead to its complete destruction.
[0004] It is an object of the present invention to provide a process for obtaining low-gloss coatings from aqueous vinyl polymer dispersions without having to use matting agents.
[0005] According to the present invention, there is provided a method for producing a coating from an aqueous radiation-curable coating composition, wherein the method comprises the following steps in order (1) to (4):
[0006] (1) applying an aqueous radiation-curable coating composition onto a surface of a substrate,
[0007] (2) drying the aqueous radiation-curable coating composition to provide an at least partially dried coating composition,
[0008] (3) irradiating the at least partially dried coating composition with ultraviolet light having a wavelength of ≤220 nm under an inert atmosphere, and then
[0009] (4) Irradiation with ultraviolet light with a wavelength of ≥300nm or electron beam,
[0010] The aqueous radiation-curable coating composition is a dispersion comprising:
[0011] (A) at least one aqueous dispersion of at least one vinyl polymer (A), wherein
[0012] The polymer system (A) comprises a glass transition temperature T g A vinyl polymer having a temperature of less than or equal to 77°C, wherein T is determined by differential scanning calorimetry as described in the specification g ,
[0013] The polymer system (A) is substantially free of radiation-curable ethylenically unsaturated bonds, and
[0014] The polymer system (A) has an acid value of 5 to 105 mg KOH / gram (A),
[0015] (B) at least one radiation-curable diluent (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 to 3, and
[0016] (C) water and optionally an organic solvent, whereby the optional organic solvent is present in an amount of up to 30% by weight, based on the total amount of water and organic solvent,
[0017] The amount of (A) is 30 to 75% by weight, and the amount of (B) is 25 to 70% by weight, based on the total amount of (A) and (B).
[0018] It has surprisingly been found that the process of the present invention enables low gloss coatings to be obtained from aqueous radiation curable vinyl polymer dispersions as defined herein without the use of matting agents.
[0019] It has also been surprisingly found that the process of the present invention, which comprises pre-treating the coating composition with ultraviolet light having a wavelength of ≤ 220 nm (also further referred to as the excimer irradiation step), enables obtaining low gloss coatings from aqueous radiation-curable vinyl polymer dispersions as defined herein, without the use of matting agents, having improved coffee resistance and / or water resistance compared to when the dispersion contains a matting agent and this is achieved while the vinyl polymer system is substantially free of radiation-curable ethylenically unsaturated bonds. More particularly, by means of the process of the present invention, coatings having a gloss measured at 20° angle geometry of less than 10 gloss units, preferably a gloss measured at 60° angle geometry of less than 40 gloss units (further referred to as low gloss), more preferably a gloss measured at 60° angle geometry of less than 30 gloss units, more preferably a gloss measured at 60° angle geometry of less than 20 gloss units can be obtained. The aqueous radiation curable coating composition according to the present invention is capable of achieving a difference in gloss measured at 60° angular geometry in the presence and absence of an excimer irradiation step of at least 30 gloss units, preferably at least 40 gloss units, more preferably at least 50 gloss units, more preferably at least 60 gloss units.
[0020] Another advantage of the present invention is that by means of the present invention, low-gloss coatings can be obtained which have improved resistance to fingernail scratching compared to when the dispersion contains a matting agent.
[0021] Another advantage of the present invention is that no matting agents need to be handled, which is advantageous because matting agents have a large surface area and contain a large proportion of small dust-forming particles that may pose an exposure and explosion hazard. Another advantage of not having to use matting agents to obtain low-gloss coatings is that coating compositions with less or no sedimentation and thus improved storage stability can be achieved. Another advantage of the process of the present invention is that coatings with significantly higher smoothness can be obtained than when the coating contains matting particles.
[0022] WO-A-2013 / 092521 describes a method for producing uniform matte coatings on flat surfaces based on so-called 100% radiation-curable coating compositions. In this method, first, a 100% radiation-curable coating composition containing a low molecular weight radiation-curable oligomer as a binder and optionally one or more reactive diluents to reduce the viscosity is applied to the surface of a flat substrate using a spiral scraper. This wet paint layer is then irradiated with a wavelength of 200 to 420 nm and a radiation dose of 25 to 120 mJ / cm 2 The coating composition is then irradiated with ultraviolet light of 120 nm to 230 nm to cause partial gelation of the coating composition. The coating thus obtained is then irradiated with ultraviolet light from an excimer lamp having a wavelength of 120 nm to 230 nm under an inert gas, followed by final curing using a conventional UV emitter. A 100% radiation-curable coating composition refers to a coating composition having a solid content of 100% by weight. A 100% radiation-curable coating composition is a homogeneous system having only one phase, while an aqueous radiation-curable vinyl polymer coating composition as defined herein is a dispersion having at least two phases, one of which contains discrete particles (colloidally dispersed particles) distributed throughout an aqueous medium, the particles being the dispersed phase, and the aqueous medium being the continuous phase.
[0023] WO-A-2013 / 092521 does not teach that low gloss coatings can be obtained from aqueous coating compositions, let alone from aqueous radiation curable vinyl polymers as defined herein, and is silent on the stain resistance of the cured coatings.
[0024] Another disadvantage of the method described in WO-A-2013 / 092521 is that the viscosity of the 100% radiation-curable coating composition is generally high, so that some application techniques, such as spraying, are difficult or impossible to use to apply the coating composition to the substrate. Spraying application can be advantageously used to apply the coating composition to substrates with more complex shapes, such as furniture or decorative frames. The viscosity of the 100% radiation-curable coating composition can be reduced by adding a monofunctional diluent with a low molecular weight, so that a viscosity that allows the radiation-curable coating composition to be deposited on the substrate by spraying can be obtained. However, applying a 100% radiation-curable coating composition by spraying inherently results in a coating having a high coating thickness.
[0025] Another advantage of using an aqueous radiation curable vinyl polymer dispersion as defined herein is that the viscosity can be controlled by adjusting the solids content with water, so that by means of the process of the invention the coating can also be easily applied by spraying.
[0026] Another advantage of the fact that aqueous radiation curable vinyl polymer dispersions as defined herein are more easily applied by spraying is that the process of the invention also enables low gloss coatings to be obtained on articles of more complex shapes, such as decorative frames, with a more uniform gloss of the coated article.
[0027] Another advantage of using an aqueous radiation curable coating composition as defined herein is that low gloss can be imparted to coatings having relatively low thicknesses (e.g., coating thicknesses of 50 microns or even less) using the process of the present invention. Another advantage of the present invention is that the gloss of the coating can be adjusted with the residual water and / or organic solvent content present in the at least partially dried coating composition.
[0028] It has also surprisingly been found that with the coating composition as claimed, low gloss coatings can be obtained in only 2 irradiation steps (i.e. steps (3) and (4)), in particular for coatings with a wet thickness (before drying) of at most 300 microns, or at most 250 microns, or at most 200 microns or at most 175 microns, in particular at most 150 microns, more in particular at most 125 microns, more in particular at most 100 microns, more in particular at most 75 microns. WO-A-2013 / 092521 teaches that an additional partial gelling irradiation step is required before the excimer irradiation step (step (3) of the method of the invention) and the finish curing step (step (4) of the method of the invention), and thus WO-A-2013 / 092521 teaches that three irradiation steps are required to obtain a low gloss / matt coating with a homogeneous surface structure, see in particular Table 2.
[0029] The aqueous radiation curable coating composition used in the process of the present invention comprises the vinyl polymer in dispersed form, ie the composition comprises dispersed particles of the vinyl polymer.
[0030] A dispersion refers to a system having at least two phases, one of which contains discrete particles (colloidally dispersed particles) distributed throughout a bulk substance, the particles being the dispersed phase, and the bulk substance being the continuous phase. The continuous phase of an aqueous dispersion is provided at least in part by water. Preferably, the continuous phase of the dispersion of the present invention comprises at least 75% by weight, more preferably at least 80% by weight, and even more preferably at least 90% by weight of water (relative to the continuous phase).
[0031] The aqueous coating composition used in the method of the present invention is radiation curable. Radiation curable means that radiation is required to initiate crosslinking of the dispersion. The aqueous coating composition used in the method of the present invention contains ethylenically unsaturated (C=C) bond functional groups, which can crosslink by free radical polymerization under the influence of irradiation, preferably in combination with the presence of a (photo)initiator.
[0032] As used herein, the acrylate functionality of a compound is the number of acrylate functional groups per molecule of the compound.
[0033] The acrylate functional group has the formula: CH2=CH-C(O)O-.
[0034] For all upper and / or lower limits of any range given herein, unless otherwise specifically stated, the boundary values are included in the given range. Thus, when reference is made to x to y, x and y and all intermediate values are included.
[0035] Polymer system (A)
[0036] The polymer system (A) comprises one or more glass transition temperatures T 2 in an amount of at least 50% by weight, preferably at least 55% by weight, more preferably at least 60% by weight, more preferably at least 65% by weight, based on the amount of the polymer system (A). g The glass transition temperature T is determined by differential scanning calorimetry as further described herein. g Therefore, the glass transition temperature T g The amount of the vinyl polymer having a temperature of 77°C or less is 50 to 100% by weight, preferably 55 to 100% by weight, more preferably 60 to 100% by weight, and even more preferably 65 to 100% by weight; and the glass transition temperature T g The amount of vinyl polymer above 77°C is 0 to 50% by weight, preferably 0 to 45% by weight, more preferably 0 to 40% by weight, and even more preferably 0 to 35% by weight, whereby the glass transition temperature T gVinyl polymers having a glass transition temperature T less than or equal to 77°C g The total amount of vinyl polymers above 77° C. is preferably 100% by weight. Therefore, the polymer system preferably consists of a glass transition temperature T g A vinyl polymer having a glass transition temperature T less than or equal to 77°C and optionally g Vinyl polymer composition above 77°C.
[0037] The polymer system (A) in the aqueous radiation curable coating composition used in the present invention has a theoretical acid value of 5 to 105 mg KOH / gram (A). The polymer system (A) preferably has an acid value of less than 95 mg KOH / gram (A), more preferably less than 85 mg KOH / gram (A), and even more preferably less than 75 mg KOH / gram (A).
[0038] As used herein, the acid value of polymer system (A) is a theoretical acid value and is calculated according to the formula: AV = ((grams of acid monomer / grams of total monomers used to prepare polymer system (A) / molecular weight of acid monomer)*56.1)*1000 and expressed as mg KOH / gram (A).
[0039] The polymer system (A) present in the aqueous radiation-curable coating composition used in the present invention is substantially free of radiation-curable ethylenically unsaturated bonds. As used herein, the polymer system (A) substantially free of radiation-curable ethylenically unsaturated bonds means that the concentration of radiation-curable ethylenically unsaturated bonds (also referred to as C=C bond concentration) of the polymer system (A) present in the aqueous radiation-curable coating composition of the present invention is less than 0.50 meq C=C / gram of polymer system (A), preferably less than 0.40 meq C=C / gram of polymer system (A), more preferably less than 0.30 milliequivalent C=C / gram of polymer system (A), more preferably less than 0.20 milliequivalent C=C / gram of polymer system (A), more preferably less than 0.10 milliequivalent C=C / gram of polymer system (A). As used herein, the amount of radiation-curable ethylenically unsaturated bonds in polymer system (A) is measured by iodometric titration, i.e. by titration after adding a fixed excess of dodecyl mercaptan solution (0.25 N) (isopropanol IPA / toluene as solvent and KOH as catalyst) on the unsaturated groups; it is allowed to react for 3 minutes (base-catalyzed Michael addition of the mercaptan to the double bonds). Acetic acid is then added to neutralize the KOH and an excess of iodine solution (0.1 N) on dodecyl mercaptan is added. The residual iodine is then titrated with sodium thiosulfate using a platinum electrode. Most preferably, polymer system (A) does not contain radiation-curable ethylenically unsaturated bonds.
[0040] Vinyl polymers herein generally refer to polymers derived from addition polymerization (generally by free radical processes) of at least one ethylenically unsaturated monomer. Thus, vinyl monomers herein refer to ethylenically unsaturated monomers.
[0041] The at least one vinyl polymer of the vinyl polymer system is preferably obtained by solution, emulsion or suspension polymerization. In the case of obtaining the vinyl polymer by solution polymerization, the applied solvent, preferably a volatile solvent, is removed during and / or after the emulsification of the vinyl polymer. Preferably, the method for preparing the at least one vinyl polymer does not contain an organic solvent. Therefore, the at least one vinyl polymer is preferably obtained by emulsion or suspension polymerization. Most preferably, the at least one vinyl polymer is obtained by emulsion polymerization, and the at least one vinyl polymer is preferably obtained in an aqueous emulsion polymerization process. Such aqueous emulsion polymerization processes are well known in the art per se and do not require detailed description. It can be said that such a method involves polymerizing monomers in an aqueous medium and using an initiator that generates free radicals for polymerization and (usually) using appropriate heating (e.g. 30 to 120° C.) and stirring (agitation). Aqueous emulsion polymerization can be carried out using one or more conventional emulsifiers, which are surfactants. Anionic, nonionic and anionic-nonionic surfactants, as well as combinations of these three types, can be used; cationic surfactants can also be used.
[0042] In the case of preparing at least one vinyl polymer by emulsion polymerization, a free radical polymerization for obtaining the vinyl copolymer (A) is carried out using a free radical initiator, appropriate heating and stirring (agitation). The polymerization can use conventional free radical initiators [such as hydrogen peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, persulfates such as ammonium persulfate, potassium persulfate and sodium persulfate]; redox systems can be used; combinations such as tert-butyl hydroperoxide, isoascorbic acid and FeEDTA are useful; based on the weight of the total monomer loaded, the amount of the initiator or initiator system is generally 0.05 to 3%. The molecular weight of the vinyl copolymer (A) can be controlled by using a well-known chain transfer agent. Preferred chain transfer agents may include mercaptans and alkyl halides. More preferably, the chain transfer agent is selected from lauryl mercaptan, 3-mercaptopropionic acid, isooctyl thioglycolate, mercaptoethanol, tetrabromomethane or tribromoform. The most preferred chain transfer agent is a mercaptan selected from lauryl mercaptan, 3-mercaptopropionic acid, isooctyl thioglycolate and mercaptoethanol.
[0043] The polymerization of the vinyl monomers to form the polymer system (A) can be carried out in different ways. Straight emulsions with only one monomer feed, sequential polymers resulting in a phase-separated particle morphology and oligomer-polymer emulsions in which one of the preferred polymer phases contains significantly more acid functionality than the other phase can be envisaged.
[0044] The polymer system may have a phase-separated particle morphology obtained by polymerization of at least a first monomer feed and a different second monomer feed. The polymer system (A) preferably comprises at least two vinyl polymers. In case the polymer system (A) comprises at least two vinyl polymers, preferably the glass transition temperatures (T g ) differ by at least 20° C., more preferably by at least 30° C., more preferably by at least 40° C., more preferably by at least 50° C., more preferably by at least 60° C., and preferably by at most 200° C., more preferably by at most 150° C. In one embodiment of the present invention, polymer system (A) comprises at least two vinyl polymers having a difference in acid number, wherein one vinyl polymer has an acid number of at least 13 mg KOH / gram of vinyl polymer, and at least one other vinyl polymer preferably has an acid number of not more than 13 mg KOH / gram of vinyl polymer.
[0045] The emulsion polymerization for producing the at least one vinyl polymer may be carried out using an "all-in-one" batch process (i.e. a process in which all the materials to be used are present in the polymerization medium at the start of the polymerization) or a semi-batch process (in which one or more of the materials used (usually at least one monomer) are fed fully or partly into the polymerization medium during the polymerization). In-line mixing of two or more of the materials used may also be used.
[0046] The pH of the final polymer emulsion containing polymer system (A) is preferably from 5 to 9, more preferably from 7 to 9. In the case of an emulsion polymerization process, it is preferred to use ammonia, an organic amine or an inorganic base to raise the pH during the monomer feed or at the end of the polymerization. Preferred bases are ammonia, dimethylethanolamine and hydroxide salts of lithium, sodium or potassium. The most preferred base is ammonia.
[0047] The polymer system (A) preferably has a weight average molecular weight M of at least 5,000 g / mol, more preferably at least 10,000 g / mol, even more preferably at least 20,000 g / mol, even more preferably at least 30,000 g / mol. wThe upper limit of the weight average molecular weight is not critical, but is preferably at most 1,000,000 g / mol, more preferably at most 500,000 g / mol, and even more preferably at most 250,000 g / mol. The weight average molecular weight M is determined as further described herein. w .
[0048] The vinyl polymer of the vinyl polymer system (A) is preferably an acrylic polymer. The term acrylic polymer as used herein refers to a polymer obtained by polymerization of at least one polymer precursor comprising an acrylate (-HC=CHC(=O)O-) and / or methacrylate (-HC=C(CH3)C(=O)O-) moiety to obtain an acrylic polymer comprising -(CH2-CHC(=O)O-)- and / or -(CH2-C(CH3)C(=O)O-)- moieties. The acrylic polymer may contain other moieties, including arylalkylenes, such as styrene, although in one embodiment of the present invention, it is preferred that the composition is substantially free of arylalkylenes.
[0049] The polymer system (A) preferably comprises
[0050] (A1) a carboxylic acid-functional ethylenically unsaturated monomer, and
[0051] (A2) an ethylenically unsaturated monomer different from (A1).
[0052] Monomer (A1) is preferably selected from itaconic acid, itaconic anhydride, itaconic acid monoalkyl esters, itaconic acid monoaryl esters, acrylic acid, methacrylic acid, β-carboxyethyl acrylate and combinations thereof, more preferably, monomer (A1) is acrylic acid and / or methacrylic acid, most preferably, monomer (A1) is methacrylic acid.
[0053] Monomer (A2) is preferably selected from acrylates, methacrylates, arylalkylenes, itaconates and any mixtures thereof. Preferably at least 30% by weight, more preferably at least 40% by weight, more preferably at least 50% by weight, more preferably at least 60% by weight, and even more preferably at least 70% by weight of the total amount of monomer (A2) is selected from methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-octyl acrylate, styrene and a mixture of two or more of the monomers. Preferably at least 30% by weight, more preferably at least 40% by weight, more preferably at least 50% by weight, more preferably at least 60% by weight, and even more preferably at least 70% by weight of the total amount of monomer (A2) is selected from methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-octyl acrylate and a mixture of two or more of the monomers.
[0054] Radiation curable diluent (B)
[0055] The radiation curable coating composition comprises one or more radiation curable diluents (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 or 3. In one embodiment, the radiation curable coating composition comprises one or more radiation curable diluents (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2. In another embodiment, the radiation curable coating composition comprises one or more radiation curable diluents (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 3. In yet another embodiment, the radiation curable coating composition comprises one or more radiation curable diluents (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 and one or more radiation curable diluents (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 3.
[0056] The molar mass of the radiation-curable diluent (B) is calculated from its corresponding molecular formula, which indicates the number of each type of atom in the radiation-curable diluent. Thus, the molar mass of (B) is the calculated molar mass obtained by adding the atomic masses of all atoms present in the structural formula of the compound.
[0057] The one or more acrylate diluents (B) have a molar mass of less than 750 g / mol, preferably less than 650 g / mol, more preferably at most 500 g / mol, more preferably at most 450 g / mol. The one or more acrylate diluents (B) preferably have a molar mass of at least 125 g / mol, preferably at least 150 g / mol, more preferably at least 175 g / mol, even more preferably at least 200 g / mol.
[0058] Preferred examples of the one or more acrylate diluents (B) having an acrylate functionality of 2 are trimethylolpropane diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, dipropylene glycol diacrylate, diethylene glycol diacrylate, dipropylene glycol diacrylate and any mixtures thereof. If appropriate, they may further comprise (additional) alkoxy groups, preferably propoxy groups, wherein the maximum number of alkoxy groups is such that the molar mass remains below 750 g / mol. A more preferred example of the one or more acrylate diluents (B) having an acrylate functionality of 2 is dipropylene glycol diacrylate (DPGDA) (having the corresponding molecular formula C 12 H 18O5 and its corresponding molar mass 242g / mol); dipropylene glycol diacrylate containing additional alkoxy groups, preferably propoxy groups; and any mixture thereof.
[0059] Preferred examples of the one or more acrylate diluents (B) having an acrylate functionality of 3 are trimethylolpropane triacrylate, di(trimethylolpropane) triacrylate, pentaerythritol triacrylate, glycerol propoxy triacrylate and any mixtures thereof. If appropriate, they may further comprise (additional) alkoxy groups, preferably propoxy groups, wherein the maximum number of alkoxy groups is such that the molar mass remains below 750 g / mol. More preferred examples of the one or more acrylate diluents (B) having an acrylate functionality of 3 are the corresponding acrylate diluents of formula C 21 H 32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol; di(trimethylolpropane) triacrylate containing an alkoxy group, preferably a propoxy group; having a corresponding molecular formula C 21 H 32 O9 and its corresponding glyceryl propoxy triacrylate (GPTA) with a molar mass of 428 g / mol; glyceryl propoxy triacrylate containing an additional alkoxy group, preferably a propoxy group; having a corresponding molecular formula C 14 H 18 O7 and its corresponding pentaerythritol triacrylate (PET3A) with a molar mass of 298 g / mol; pentaerythritol triacrylate containing an alkoxy group, preferably a propoxy group; having a corresponding molecular formula C 15 H 20 O6 and its corresponding trimethylolpropane triacrylate (TMPTA) with a molar mass of 296 g / mol; trimethylolpropane triacrylate containing an alkoxy group, preferably a propoxy group; and any mixture thereof.
[0060] Radiation-curable diluents (B) having an acrylate functionality of 2 or 3 preferably contain alkoxy groups, preferably propoxy groups (-C3H6O-). In the case where the radiation-curable diluent (B) contains (additional) alkoxy groups, the maximum number of alkoxy groups is such that the molar mass remains below 750 g / mol.
[0061] In a preferred embodiment of the present invention, at least 10 wt. %, preferably at least 20 wt. %, more preferably at least 30 wt. %, more preferably at least 40 wt. %, more preferably at least 50 wt. %, more preferably at least 60 wt. %, more preferably at least 70 wt. %, more preferably at least 80 wt. %, more preferably at least 90 wt. %, most preferably 100 wt. % of the radiation curable diluent (B) is selected from:
[0062] With the corresponding molecular formula C 21 H32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol,
[0063] di(trimethylolpropane) triacrylate containing an alkoxy group,
[0064] With the corresponding molecular formula C 21 H 32 O9 and its corresponding glyceryl propoxy triacrylate (GPTA) with a molar mass of 428 g / mol,
[0065] Glyceryl propoxy triacrylate containing an additional alkoxy group,
[0066] With the corresponding molecular formula C 14 H 18 O7 and its corresponding pentaerythritol triacrylate (PET3A) with a molar mass of 298 g / mol,
[0067] Pentaerythritol triacrylate containing an alkoxy group,
[0068] With the corresponding molecular formula C 15 H 20 O6 and its corresponding trimethylolpropane triacrylate (TMPTA) with a molar mass of 296 g / mol,
[0069] trimethylolpropane triacrylate containing an alkoxy group,
[0070] With the corresponding molecular formula C 12 H 18 O5 and its corresponding dipropylene glycol diacrylate (DPGDA) with a molar mass of 242 g / mol,
[0071] Dipropylene glycol diacrylate containing an additional alkoxy group,
[0072] and any mixture thereof.
[0073] Preferably, the at least one radiation-curable diluent (B) has an acrylate functionality of two.
[0074] The radiation curable coating composition used in the process of the present invention may further comprise an acrylate diluent having a molar mass as defined for the (B) compound present in the radiation curable coating composition (i.e. below 750 g / mol, preferably at most 650 g / mol, more preferably at most 500 g / mol, more preferably at most 450 g / mol, preferably at least 125 g / mol, more preferably at least 150 g / mol, more preferably at least 175 g / mol, even more preferably at least 200 g / mol) but having an acrylate functionality different from that defined for (B), for example having an acrylate functionality of 1, 4 or 5. Such an acrylate diluent is preferably present in the radiation curable coating composition in an amount such that the average acrylate functionality of the acrylate diluent having a molar mass as defined for (B) is in the range of preferably 1.8 to 3.2. As used herein, the average acrylate functionality of the acrylate diluent having a molar mass as defined for (B) is where w k is the molar mass M as defined for (B) present in the radiation curable coating composition k and having an acrylate functionality f which may be as defined for (B) or lower or higher than as defined for (B) k The amount of acrylate diluent in g. We illustrate the calculation of the average acrylate functionality using a theoretical example: For a formulation consisting of 60 g of vinyl polymer, 30 g of DPGDA (molar mass 242 g / mol and acrylate functionality 2), 10 g of Di-TMPTA (molar mass 466 g / mol and acrylate functionality 4) and 2.5 g of photoinitiator: The sum of component k includes only DPGDA and Di-TMPTA, and the calculated average functionality of the acrylate diluent for this theoretical formulation is
[0075] Preferably, the radiation curable coating composition used in the process of the present invention comprises a monofunctional diluent in an amount of less than 7 wt.-%, more preferably less than 5 wt.-%, more preferably less than 3 wt.-%, more preferably less than 1 wt.-%, most preferably less than 0.5 wt.-% relative to the weight of the entire radiation curable coating composition.
[0076] The amounts of (A) and (B) in the aqueous radiation-curable coating composition can vary within wide ranges, since water and optionally organic solvents can be used to adjust the viscosity and to adjust the layer thickness of the applied coating. Preferably, the amount of (A) is 35 to 75% by weight and the amount of (B) is 25 to 65% by weight, based on the total amount of (A) and (B), preferably, the amount of (A) is 35 to 70% by weight and the amount of (B) is 30 to 65% by weight, more preferably, the amount of (A) is 35 to 65% by weight and the amount of (B) is 35 to 65% by weight, more preferably, the amount of (A) is 40 to 65% by weight and the amount of (B) is 35 to 60% by weight, most preferably, the amount of (A) is 40 to 60% by weight and the amount of (B) is 40 to 60% by weight.
[0077] The total amount of (A) and (B) is preferably 10 to 60 wt%, more preferably 15 to 50 wt%, more preferably 15 to 45 wt%, even more preferably 20 to 40 wt%, even more preferably 25 to 35 wt%, based on the total weight of the aqueous radiation curable coating composition.
[0078] The amount of water in the aqueous radiation curable coating composition is preferably at least 30 wt%, or at least 35 wt%, or at least 40 wt%, or at least 45 wt%, or at least 50 wt%, or at least 55 wt%, or at least 60 wt%, or at least 70 wt%, based on the total weight of the aqueous radiation curable coating composition.
[0079] The optional organic solvent is present in the aqueous radiation curable coating composition in an amount of up to 30 wt. %, preferably up to 25 wt. %, more preferably up to 20 wt. %, more preferably up to 15 wt. %, more preferably up to 10 wt. %, more preferably up to 5 wt. %, more preferably up to 4 wt. %, more preferably up to 3 wt. %, more preferably up to 2 wt. %, more preferably up to 1 wt. %, wherein the amount of organic solvent is given based on the total amount of water and organic solvent present in the aqueous radiation curable coating composition. Suitable organic solvents are solvents which are inert towards the functional groups present in the coating composition. Suitable solvents are, for example, hydrocarbons, alcohols, ketones and esters, such as cosolvents which also have the function of a coalescing agent, such as 1-methyl-2-pyrrolidone, glycols and glycol ethers, such as butyl diglycol, dipropylene glycol methyl ether, acetone, methyl ethyl ketone and alkyl ethers of glycol acetates or mixtures thereof, and ester alcohols, such as 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Texanol). Most preferably, the aqueous radiation-curable coating composition is substantially free of organic solvents, i.e. preferably no organic solvents have been intentionally added to the aqueous radiation-curable coating composition (i.e. small amounts of organic solvents may be present in the additives used to prepare the composition).
[0080] The viscosity of the dispersion consisting of (A), (B) and (C) and containing 10 to 60 wt. % of (A) and (B), relative to the total amount of (A), (B) and (C), is preferably 10 to 1000 MPa.s, or 10 to 800 MPa.s, or 10 to 500 MPa.s. The viscosity is determined as further described herein.
[0081] The z-average particle size of the dispersion consisting of (A), (B) and (C) is preferably from 20 to 1000 nm, more preferably from 25 to 500 nm, even more preferably from 25 to 250 nm, most preferably from 30 to 200 nm, whereby the z-average particle size is determined as further described herein.
[0082] The coating composition generally further contains an additive compound; that is, a collection of one or more than one individual additives having one or more than one specified structure or type. Suitable additives are, for example, light stabilizers, such as ultraviolet absorbers and reversible free radical scavengers (HALS), photosensitizers, antioxidants, degassing agents, wetting agents, emulsifiers, slip additives, waxes, inhibitors, adhesion promoters, flow control agents, film formers, rheological aids such as thickeners, flame retardants, corrosion inhibitors, waxes, desiccants and biocides. One or more of the above additives may be used in any suitable amount in the coating composition used in the method of the present invention, and may be selected individually or in combination of one or more types listed herein. In a preferred embodiment, the additive compound is present in an amount of about 0 wt % to 40 wt %, or 0 wt % to 30 wt %, or 0 wt % to 20 wt %, or 0 wt % to 10 wt %, or 0 wt % to 5 wt %; or 0.01 wt % to 40 wt %; or 0.01 wt % to 30 wt %, or 0.01 wt % to 20 wt %, or 0.01 wt % to 10 wt %, or 0.01 wt % to 5 wt %, or 0.1 wt % to 2 wt %, relative to the total weight of the radiation curable coating composition. Another advantage of the present invention is that the coating composition can also be colored, and this does not significantly complicate the application of the coating composition on the substrate. The coating composition then contains at least one pigment. In the art, titanium dioxide (TiO ) is considered to be a commercially important white pigment. Despite the porous nature of pigments of this type, it has also been surprisingly found that the presence of pigments of this type in a coating composition as defined herein hardly impairs the coffee, red wine and / or mustard resistance of the coating, or only deteriorates it to such an extent that the resistance to coffee, red wine and / or mustard remains at an acceptable level.
[0083] The coating composition may also contain one or more inorganic fillers. The coating composition may also contain external matting agents with an additional matting effect, but this is not preferred. Suitable external matting agents are, for example, inorganic silica or organic waxes. The maximum amount of external matting agent is preferably at most 1.5 wt. %, more preferably at most 1 wt. %, most preferably at most 0.5 wt. %, relative to the total weight of the coating composition.
[0084] The method of the present invention optionally includes a pre-curing step (2a). Carrying out the pre-curing step (2a) may be beneficial to improve adhesion, in particular to improve inter-coat adhesion. In this optional step (2a), pre-curing of the at least partially dried coating composition is achieved to provide an at least partially cured coating composition. In the optional step (2a), some reactive ethylenically unsaturated double bonds of the curable compound are polymerized in the uncured coating so that the coating is partially cured but not yet fully cured. This process is also referred to as pre-curing.
[0085] Therefore, the method of the present invention comprises the following steps in the order (1), (2), (2a), (3) and (4):
[0086] (1) applying an aqueous radiation-curable coating composition onto a surface of a substrate,
[0087] (2) drying the aqueous radiation-curable coating composition to provide an at least partially dried coating composition,
[0088] (2a) optionally by irradiating with ultraviolet light having a wavelength of 300 to 450 nm, preferably 300 to 420 nm, at a dose of 20 to 200 mJ / cm 2 The radiation dose is preferably 30 to 100 mJ / cm 2 irradiating the at least partially dried coating composition with a radiation dose of 1000 Å to pre-cure the at least partially dried coating composition to provide an at least partially cured coating composition,
[0089] (3) irradiating the at least partially dried coating composition or the at least partially cured coating composition with ultraviolet light having a wavelength of ≤220 nm, preferably a wavelength of ≥120 nm, more preferably ≥150 nm, and particularly preferably 172 nm or 195 nm under an inert atmosphere, and then
[0090] (4) Irradiation with ultraviolet light of wavelength ≥ 300 nm or electron beam.
[0091] In step (1) of the method of the present invention, the aqueous radiation-curable coating composition is applied to the substrate by methods known to those skilled in the art (e.g., knife coating, brush coating, roller coating, spray coating). The coating composition is applied to the substrate in a coating thickness (before drying) of preferably 5 to 300 microns, more preferably 15 to 175 microns, more preferably 20 to 150 microns, more preferably 25 to 125 microns.
[0092] In step (2) of the process of the present invention, the drying of the aqueous radiation curable coating composition applied to the substrate is preferably carried out at a temperature above 30° C. to evaporate water and optionally organic solvents and other volatile compounds to provide an at least partially dried coating composition. The term "drying" refers to the loss of water and, if present, organic solvents and other volatile compounds, such as neutralizing agent amines, from the aqueous coating composition by evaporation to an extent that preferably at least 80% by weight of the water is removed.
[0093] The irradiation in the optional pre-curing step (2a) is preferably carried out under atmospheric conditions, in other words not under inert gas conditions and / or not in an oxygen-reduced atmosphere. Suitable radiation sources for the ultraviolet light in the specified wavelength range in step (2a) are UV-A emitting radiation sources (e.g. fluorescent tubes, LED lamps), high-pressure or medium-pressure mercury vapor lamps (wherein the mercury vapor can be modified by doping with other elements such as gallium or iron), pulsed lamps (so-called UV flash lamps) or halogen lamps. In a preferred embodiment of the present invention, the process is carried out without step (2a), i.e. the curing of the radiation-curable coating composition is carried out in only two irradiation steps, i.e. steps (3) and (4)).
[0094] A suitable radiation source for step (3) is an excimer UV lamp which emits UV light with a wavelength of ≤220 nm, preferably ≥120 nm, more preferably ≥150 nm, and particularly preferably 172 nm or 195 nm. The radiation dose used in step (3) is usually in the range of 0.1 to 150 mJ / cm 2 , preferably 1 to 100 mJ / cm 2 , more preferably 1 to 20 mJ / cm 2 , more preferably 2 to 15 mJ / cm 2. Step (3) must be carried out in an inert gas atmosphere. An inert gas atmosphere is understood to mean an essentially oxygen-free atmosphere, i.e. an atmosphere containing less than 0.5% by volume of oxygen, preferably less than 0.1% by volume of oxygen, and particularly preferably less than 0.05% by volume of oxygen. Typically, an inert gas atmosphere is achieved by purging the area exposed to UV radiation with an inert gas stream. An inert gas atmosphere prevents unwanted ozone formation on the one hand and inhibits the polymerization of the paint layer on the other hand. Examples of inert gases are nitrogen, helium, neon or argon. Particularly preferably, nitrogen is used. This nitrogen should contain only very small amounts of foreign gases, such as oxygen, preferably with a purity grade of <300 ppm oxygen.
[0095] In step (4) of the method of the present invention, the coating obtained in step (3) is irradiated with ultraviolet light having a wavelength ≥ (higher than or equal to) 300 nm or with electron beams to achieve a major or preferably complete polymerization of the radiation curable compounds of the coating composition, so that the coating is preferably completely cured. In the case of applying electron beam irradiation (150 to 300 kV) in step (4), a dose of 10 to 100 kGy, preferably 20 to 50 kGy, is generally applied. In step (4), ultraviolet irradiation is preferred, preferably with a wavelength of 300 to 420 nm and preferably with a power of 100 to 2000 mJ / cm 2 , more preferably 150 to 1500 mJ / cm 2 The radiation dose of the coating composition is preferably 0.1 to 5% by weight of the coating composition. High-pressure and medium-pressure mercury vapor lamps can be used in particular as ultraviolet radiation sources, wherein the mercury vapor can be doped with other elements, such as gallium or iron. Step (4) can also be optionally carried out in an inert gas atmosphere. In the case of applying ultraviolet radiation in step (4), the radiation-curable coating composition comprises a photoinitiator. If the radiation-curable coating composition of the present invention comprises one or more photoinitiators, they are included in an amount sufficient to obtain the desired curing response. Typically, the one or more photoinitiators are included in an amount of 0.1 to 5% by weight of the entire coating composition. Preferably, the one or more photoinitiators are present in an amount of 0.25% to 4% by weight, more preferably 0.5% to 3.5% by weight, and even more preferably 0.5% to 3% by weight, relative to the total weight of the coating composition.
[0096] Photoinitiator is a compound that chemically changes to produce at least one of free radicals, acids and bases due to the action of light or the synergistic effect between the action of light and the electronic excitation of the sensitizing dye. Well-known types of photoinitiators include cationic photoinitiators and free radical photoinitiators. According to one embodiment of the present invention, the photoinitiator is a free radical photoinitiator.
[0097] In one embodiment, the photoinitiator compound includes, consists of, or consists essentially of one or more acylphosphine oxide photoinitiators. Acylphosphine oxide photoinitiators are known and disclosed, for example, in U.S. Pat. Nos. 4,324,744, 4,737,593, 5,942,290, 5,534,559, 6,020,529, 6,486,228, and 6,486,226. Preferred types of acylphosphine oxide photoinitiators for the photoinitiator compound include bisacylphosphine oxide (BAPO) or monoacylphosphine oxide (MAPO). More specifically, examples include 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide (CAS#84434-11-7) or 2,4,6-trimethylbenzoyldiphenylphosphine oxide (CAS#127090-72-6).
[0098] In a preferred embodiment, the photoinitiator compound may also optionally comprise, consist of, or consist essentially of an α-hydroxyketone photoinitiator. For example, suitable α-hydroxyketone photoinitiators are α-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)propanone, 2-hydroxy-2-methyl-1-(4-dodecylphenyl)propanone, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, and 2-hydroxy-2-methyl-1-[(2-hydroxyethoxy)phenyl]propanone.
[0099] In another embodiment, the photoinitiator compound comprises, consists of, or consists essentially of: α-amino ketones, such as 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-(4-methylbenzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, or 2-benzyl-2-(dimethylamino)-1-[3,4-dimethoxyphenyl]-1-butanone; benzophenones, such as benzophenone, 2,4,6-trimethylbenzophenone, 4-methylbenzophenone, 2-methylbenzophenone, 2-methoxycarbonyldi ... benzophenone, 4,4'-bis(chloromethyl)-benzophenone, 4-chlorobenzophenone, 4-phenylbenzophenone, 4,4'-bis(dimethylamino)-benzophenone, 4,4'-bis(diethylamino)benzophenone, methyl 2-benzoylbenzoate, 3,3'-dimethyl-4-methoxybenzophenone, 4-(4-methylphenylthio)benzophenone, 2,4,6-trimethyl-4'-phenyl-benzophenone or 3-methyl-4'-phenyl-benzophenone; ketal compounds, for example 2,2-dimethoxy-1,2-diphenyl-ethanone; and monomeric or dimeric benzoylformates, such as methylbenzoylformate, 5,5'-oxo-bis(vinyloxydicarbonylphenyl) or 1,2-(benzoylcarboxy)ethane.
[0100] Other suitable photoinitiators for use in the photoinitiator compound include oxime esters, such as those disclosed in US Pat. No. 6,596,445. Another class of suitable photoinitiators for use in the photoinitiator compound include, for example, phenyl glyoxylates, such as those disclosed in US Pat. No. 6,048,660.
[0101] In another embodiment, the photoinitiator compound may comprise, consist of, or consist essentially of one or more alkyl-, aryl-, or acyl-substituted compounds not mentioned above.
[0102] According to another embodiment, the composition may contain a photoinitiator that is an alkyl-, aryl- or acyl-substituted compound. In one embodiment, the alkyl-, aryl- or acyl-substituted photoinitiator has or is centered on a carbon group (Group 14) atom. In this case, upon excitation (by absorbing radiation), the Group 14 atom present in the photoinitiator compound forms a free radical. Such a compound can therefore produce a free radical having or being centered on an atom selected from silicon, germanium, tin and lead. In one embodiment, the alkyl-, aryl- or acyl-substituted photoinitiator is an acylgermanium compound. Such photoinitiators are described in US9708442. Known specific acylgermanium photoinitiators include benzoyltrimethylgermane (BTG), tetraacylgermane or bisacylgermane (which can be used as Purchased from Ivoclar Vivadent AG, 9494 Schaan / Liechtenstein).
[0103] Photoinitiators can be used alone or in combination as a blend. Suitable photoinitiator blends are disclosed, for example, in U.S. Patent No. 6,020,528 and U.S. Patent Application No. 60 / 498,848. According to one embodiment, the photoinitiator compound includes, for example, a photoinitiator blend of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (CAS#162881-26-7) and 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide (CAS#84434-11-7) in a weight ratio of about 1:11, 1:10, 1:9, 1:8 or 1:7.
[0104] Another particularly suitable photoinitiator blend is a mixture of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide and 2-hydroxy-2-methyl-1-phenyl-1-propanone (CAS#7473-98-5), for example, in a weight ratio of about 3:1:15 or 3:1:16 or 4:1:15 or 4:1:16. Another suitable photoinitiator blend is a mixture of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2-hydroxy-2-methyl-1-phenyl-1-propanone, for example, in a weight ratio of about 1:3, 1:4 or 1:5.
[0105] One or more of the above-mentioned photoinitiators may be used in the photoinitiator compound in the composition according to the invention in any suitable amount and may be selected individually or in combination of one or more types listed herein. In a preferred embodiment, the photoinitiator compound comprises, consists of or consists essentially of a free radical photoinitiator, which is preferably of the α-cleavage type.
[0106] Suitable substrates for the method according to the invention are, for example, mineral substrates such as fiber cement boards, wood, wood-containing materials, paper (including paperboard), textiles, leather, metals, thermoplastic polymers, thermosetting materials, ceramics, glass. Suitable thermoplastic polymers are, for example, polyvinyl chloride PVC, polymethyl methacrylate PMMA, acrylonitrile-butadiene-styrene ABS, polycarbonate, polypropylene PP, polyethylene PE, polyamide PA, polyethylene terephthalate PET and polystyrene PS. Suitable thermosetting materials are, for example, linoleum, epoxy resins, melamine, novolac resins, polyesters and urea-formaldehyde.
[0107] The substrate is optionally pretreated and / or optionally precoated. For example, a thermoplastic film may be treated with a corona discharge or precoated with a primer prior to application. Mineral building materials are also typically provided with a primer prior to application of the coating composition.
[0108] The coatings obtained in the process of the invention can advantageously be used for floor or wall coverings or for automotive interiors or furniture.
[0109] By means of the process of the invention, low gloss coatings can advantageously be obtained at a dry thickness of at least 2 microns, or at least 3 microns, or at least 4 microns and at most 100 microns, or at most 75 microns, or at most 50 microns.
[0110] The present invention further relates to an aqueous radiation curable coating composition as described above. The present invention further relates to a coated substrate obtained by coating a substrate with a process as described above.
[0111] The invention will now be illustrated with reference to the following examples. Unless otherwise indicated, all parts, percentages and ratios are by weight.
[0112] Method for calculating dry film thickness
[0113] The dry film thickness is calculated by multiplying the wet film thickness by the solids content of the formulation used.
[0114] DFT = WFT * solid content / 100
[0115] in
[0116] DFT: Dry film thickness in μm
[0117] WFT: wet film thickness in μm
[0118] Solid content (wt%): total weight of all solid compounds present in a formulation divided by (total weight of the formulation*100).
[0119] Measurement method
[0120] Average particle size PS:
[0121] The intensity average particle size, z-average, was determined by photon correlation spectroscopy using a Malvern Zetasizer Nano ZS. The sample was diluted in demineralized water to a concentration of approximately 0.1 g dispersion / liter. The measurement temperature was 25°C. The laser incident angle was 173°. The laser wavelength was 633 nm.
[0122] pH
[0123] The pH was measured using a Metrohm pH meter.
[0124] Solid content
[0125] The solids content of the dispersions was measured on a HB43-S halogen moisture analyzer from Mettler Toledo at a temperature of 130°C.
[0126] Viscosity
[0127] Viscosity was measured using a Brookfield LV (spindle 2, 60 rpm, room temperature).
[0128] Glossiness
[0129] Gloss is measured in the drawdown direction according to ISO 2813 and is expressed in gloss units (GU).
[0130] Stain resistance
[0131] Stain resistance tested according to IKEA IOS-MAT-066R2&R0.
[0132] Nail scratch resistance
[0133] Use the tip of a fingernail to make quick, smooth strokes across the coating with increasing pressure. Scratch resistance is rated on a scale of 0 to 5, where 0 = severe damage to the coating and 5 = no visible marks.
[0134] Differential Scanning Calorimetry (DSC)
[0135] The thermal properties of the samples were studied under a nitrogen atmosphere using a DSC250 from TA Instruments. Indium was used for enthalpy and temperature calibration of the instrument, and an empty Tzero aluminum pan was used as a reference. The thermal transitions of the samples were studied using the temperature program described in the table below. The first heating curve was used to extract the Tg data.
[0136] In the case where the polymer system contains two or more phases with different Tg, the phase ratio is calculated by calculating the heat capacity (Cp) for each Tg transition from the heat flow curve, adding them, and then calculating the relevant amounts of the different phases. For example, when the polymer system has two phases with different Tg, the amounts are calculated as Cp1 / (Cp1+Cp2)*100% and Cp2 / (Cp1+Cp2)*100%.
[0137] DSC temperature program
[0138]
[0139] The DSC samples were dried overnight under air at 120° C. Approximately 5 mg of sample was sealed in a Tzero aluminum pan.
[0140] Determination of number average molecular weight, weight average molecular weight, z average molecular weight and molecular weight distribution
[0141] The number average molecular weight, weight average molecular weight, z average molecular weight and molecular weight distribution were determined by size exclusion chromatography in THF HAC 0.8% at 40°C on a Waters Alliance 2695LC system with a Waters 2410DRI detector using two PLgel 10 μm Mixed-C columns. Tetrahydrofuran (THF HAC 0.8%) containing 0.8% v / v acetic acid 100% was used as the eluent at a flow rate of 1 mL / min. The samples were dissolved in the eluent using a concentration of 5 mg polymer / mL solvent. The solubility was judged with a laser pen after stabilization for 24 hours at room temperature; if any scattering was visible, the sample was first filtered and 150 μl of the sample solution was injected (0.45 micron PTFE filter). M was calculated using narrow polystyrene standards ranging from 162 to 1.730.000 Da. W (weight average molecular weight), M z (z-average molecular weight) and MWD (molecular weight distribution) results.
[0142] Components and abbreviations used :
[0143] DPGDA=Agisyn TM 2833, dipropylene glycol diacrylate available from Covestro
[0144] GPTA=Agisyn TM 2837, propoxylated (3) glyceryl triacrylate available from Covestro
[0145] TMPTA = trimethylolpropane triacrylate available from Covestro
[0146] DPHA=Agisyn TM2830L, dipentaerythritol hexaacrylate available from Covestro
[0147] Omnirad 500 = photoinitiator available from IGM
[0148] BYK 346 = surfactant available from BYK (45% solids)
[0149] Airex 902W = defoamer available from Evonik (24% solids)
[0150] Gel L 75N = rheology modifier available from Borchers (50% solids)
[0151] TS100 = Silica matting agent from Evonik
[0152] MEK = methyl ethyl ketone available from Aldrich
[0153] MMA = methyl methacrylate available from Aldrich
[0154] n-BA = n-butyl acrylate available from Aldrich
[0155] MAA = methacrylic acid available from Aldrich
[0156] AA = acrylic acid available from Aldrich
[0157] S = styrene available from Aldrich
[0158] 2-EHA- = 2-ethylhexyl acrylate available from Aldrich
[0159] AMBN = 2,2'-azobis(2-methylpropionitrile) available from Aldrich
[0160] SLS = Sodium dodecyl sulfate available from Aldrich
[0161] AP = ammonium persulfate available from Aldrich
[0162] KOH = Potassium hydroxide available from Aldrich
[0163] n-DM = n-dodecyl mercaptan available from Bruno Bock GMBH
[0164] Description of the commercial adhesive used
[0165] Neocryl XK-82 is a high molecular weight, medium Tg, single phase styrene-acrylic adhesive available from Covestro. The measured Tg (DSC) is 49°C. Acid value: 50.1 mg KOH / g solid. Solids content is 40 wt%.
[0166] Neocryl XK-85 is a low molecular weight, medium Tg, single phase styrene-acrylic adhesive available from Covestro. The measured Tg (DSC) is 31°C. Acid value: 45.5 mg KOH / g solid. Solids content is 40 wt%.
[0167] Neocryl XK-110 is a multiphase OH-functional acrylic adhesive prepared by gradient polymerization with controlled molecular weight and two theoretical Tgs. The measured Tg (DSC) is 49°C. Acid value: 15.6 mg KOH / g solid. Solid content is 46.5 wt%.
[0168] Neocryl XK-14 is a multiphase styrene-acrylic adhesive having a high molecular weight phase and a low molecular weight phase and a low Tg polymer phase and a high Tg polymer phase. Acid value: 13.7 mg KOH / g solid. Solid content is 40 wt%.
[0169] Neocryl XK-102 is an OH functional acrylic adhesive with an acid value of 31.2 mg KOH / g solid and a solid content of 40 wt%.
[0170] Table 1 .Specifications of commercial adhesives used.
[0171]
[0172] *T in XK-14 g The amount of vinyl polymer at 32.6°C was higher than 50% by weight.
[0173] Preparation of solution type acrylic polymer SA1
[0174] Methyl ethyl ketone (MEK, 318.9 g) was loaded in a 2L kettle equipped with heating and cooling control and heated to 80°C. A solution of methyl methacrylate (MMA, 558.6 g), n-butyl acrylate (n-BA, 413.8 g), methacrylic acid (MAA, 62.1 g) and 2,2'-azobis(2-methylpropionitrile) (AMBN, 10.4 g) was prepared in a feed tank. The monomer feed was added over 180 minutes at 80°C. After the monomer feed was completed, the feed tank was rinsed with methyl ethyl ketone (MEK, 31.0 g), and the reaction mixture was kept at 80°C for 60 minutes. Next, 2,2'-azobis(2-methylpropionitrile) (AMBN, 5.2 g) was added, and the reaction mixture was kept at 80°C for another 60 minutes. MEK was finally added to make the final solid content 54.0 wt%. The weight average molecular weight was 98.4 kDa and the number average molecular weight was 12.1 kDa. The Tg calculated according to Flory-Fox was 22°C and the acid value was 39.3 mg KOH / g solid.
[0175] Dispersion of a solution-type acrylic polymer SA1 without reactive diluent (DSA1)
[0176] Acrylic solution polymer (259.3 g, 54% solids) was heated to 40°C with stirring in a 1 L kettle equipped with heating and cooling controls. Next, triethylamine (4.9 g) was added over 5 minutes, followed by demineralized water (294.9 g) over 10 minutes. After mixing for 10 minutes, vacuum was applied and methyl ethyl ketone and water were removed until a final solids content of 30.2 wt% was reached.
[0177] Dispersion of solution-type acrylic polymer SA1 containing reactive diluent (DSA2-DSA3)
[0178] For the dispersions DSA2-DSA3 of solution-type acrylic polymers containing reactive diluents, the same method as that for preparing DSA1 was used, except that the reactive diluent (DPDGA) was added before heating to 40° C. The applied amounts of triethylamine and demineralized water are reported in Table 2.
[0179] Table 2 .Composition and specifications of DSA1 to DSA3
[0180]
[0181] Preparation of emulsion polymer EP1
[0182] A 2000 cm 3The flask was loaded with demineralized water (656.8 g) and sodium dodecyl sulfate (19.3 g of a 30 wt % aqueous solution). In a funnel, an emulsified monomer feed was prepared by mixing demineralized water (278.1 g), sodium dodecyl sulfate (28.89 g of a 30 wt % aqueous solution), styrene (S, 334.3 g), 2-ethylhexyl acrylate (2-EHA, 333.0 g), methacrylic acid (MAA, 20.64 g) and n-dodecyl mercaptan (13.8 g). In another funnel, an initiator solution was loaded by dissolving ammonium persulfate (AP, 2.3 g) in demineralized water (68.6 g) and adjusting the pH to 7.0-7.5 with 25% ammonia. The reactor was heated to 65° C. and 10 wt % of the emulsified monomer feed was added to the reactor and the reaction temperature was raised to 75° C. At 75°C, a portion of ammonium persulfate (1.2 g) dissolved in demineralized water (6.0 g) was added and allowed to exotherm. After mixing for 10 minutes, the reactor temperature was leveled at 85°C. Next, the monomer feed and initiator feed were added over a period of 150 minutes at a temperature of 83-87°C. At the end of the monomer feed, the funnel containing the monomer mixture was rinsed with demineralized water (7.4 g). The reaction was allowed to drift for 15 minutes to 80°C. Next, a solution of ammonia (25%, 4.5 g) in demineralized water (4.5 g) was added and the temperature was allowed to drift for 15 minutes. Next, the batch was cooled to 30°C and Proxel Ultra 10 (3.6 g of a 10 wt% solution) was added over 10 minutes. The pH was checked and, if necessary, adjusted to 7.8-8.0 with ammonia (12.5%). Finally, the batch was filtered through a filter cloth to remove any coagulum formed during the reaction. The solid content was 39.4% and the particle size was 72 nm. The theoretical Tg was set at 10° C. and the measured Tg (DSC) was 1.9° C. The acid value was 19.5 mg KOH / g solid.
[0183] All other binders reported in Table 3 were prepared according to the procedure described above for binder EP1 using the amounts listed in Table 3. Binders EP13 and EP14 were neutralized with KOH instead of ammonia.
[0184] Table 3. Composition and specifications of adhesives EP2 to EP14
[0185]
[0186]
[0187] Commercial adhesive formulations
[0188] Table 4. Formulations of commercial adhesives
[0189]
[0190]
[0191] Table 4 continued
[0192]
[0193] Table 5. Formulations of Dispersion Solution Type Acrylic Polymers DSA1 to DSA3
[0194] Preparation F-DSA1 F-DSA2 F-DSA3 Amount of dispersion (g) 87.40DSA1 95.81DSA2 85.00DSA3 Softened water 6.00 0.00 6.00 Byk346 0.5 0.5 0.5 TegoAirex902W 0.5 0.5 0.5 BorchiGel L75N: water (1:1) 1.08 1.00 1.02 Omnirad500 1.0 1.0 1.0 Softened water 1.52 0.00 4.98 total 100 100 100 solid(%) 28.0 27.8 27.9
[0195] Formulations of emulsion polymers EP1 to EP14
[0196] Table 6. Formulations of emulsion polymer binders EP1 to EP14
[0197]
[0198] Table 6 continued
[0199]
[0200]
[0201] Application of formulation
[0202] The coating composition thus obtained was applied onto Leneta cards (2C Leneta Inc) using a 125 μm wire bar applicator. The coated cards were dried in an oven at 50° C. for 10 minutes at an air velocity of 1.2 m / s. The coating was then cured.
[0203] Curing of the dried coating composition
[0204] Excimer / UV curing:
[0205] Immediately after drying (within 20 seconds), the formulation was cured on a UVio curing rig equipped with 2 lamps at a conveyor speed of 15 m / min. The first lamp was an Excirad 172 lamp (IOT GmbH, a xenon-based excimer lamp generating 172 nm light), under which a 11.4 mJ / cm 2The next curing step was performed with a second lamp, which was a Light Hammer 10 Mark III (Heraeus Holding, Hg-doped UV lamp) equipped with an H-bulb operating at 50% power, generating UV light with a wavelength of ≥315 nm, with a total dose of 181 mJ / cm2 as measured with a Power Puck II (EIT Inc). 2 ).
[0206] Conventional UV atmospheric curing (Conv UVcure):
[0207] Immediately after drying (within 20 seconds), the formulation was cured on a UVio curing rig at a conveyor speed of 15 m / min. The total dose was 181 mJ / cm2 as measured with a Power Puck II (EIT Inc) by a LightHammer 10 Mark III (Heraeus Holding, Hg-doped UV lamp) equipped with an H-bulb operating at 50% power. 2 ) The curing step is carried out in air.
[0208] Gloss values of commercial adhesives after excimer curing and after conventional UV curing
[0209] Table 7. Gloss values of commercial adhesive formulations after excimer curing and after conventional UV curing
[0210]
[0211] Table 7 shows that when DPHA is used as the reactive diluent, no low gloss coating is obtained after excimer cure.
[0212] Dispersion solution type acrylic polymers DSA1 to DSA3 after excimer curing and after conventional UV curing Glossiness
[0213] Table 8. Gloss values, chemical resistance and nail scratch resistance of dispersion type acrylic polymers DSA1, DSA2 and DSA3 after excimer curing and after conventional UV curing
[0214]
[0215] *nd conventional UV was not performed because the glossiness after excimer curing is already very high.
[0216] Table 8 shows that a certain amount of DPGDA is needed in combination with the dispersion solution acrylic polymer to obtain a low gloss coating after excimer cure. At this level of reactive diluent, the resulting coating exhibits improved chemical and fingernail scratch resistance.
[0217] Gloss values of the formulations of emulsion polymers EP1 to EP14
[0218] Table 9. Gloss values of emulsion polymers EP1 to EP14
[0219]
[0220] The results in Table 9 show that when the measured Tg of the emulsion polymer is > 77°C, excimer curing in the presence of 40 wt% DPGDA does not produce low gloss coatings.
[0221] Table 10. Variation of the amount of reactive diluent in Neocryl XK-82
[0222]
[0223]
[0224] Table 10 shows that 30 wt% DPGDA is required to give a low gloss coating after excimer cure. Lower amounts of reactive diluent do provide high gloss coatings.
[0225] Table 11. Changes in the type of reactive diluent in EP9
[0226]
[0227] Table 11 also shows that DPGDA and GPTA provide low gloss coatings after excimer curing, while DPHA does not. Together with the data in Table 7, this shows that excimer curing can provide low gloss coatings when DPGDA (diacrylate) or GPTA (triacrylate) are used, but the use of higher acrylates such as DPHA (hexaacrylate) does not produce low gloss coatings.
[0228] Formulations F-EP8 and F-EP9 listed in Table 6 were mixed with 1.8% Acematt TS-100 to reduce gloss. These formulations were cured with UV curing without an inert atmosphere. See Table 12.
[0229] Table 12. Comparison of gloss values, stain resistance and nail scratch resistance of adhesive dispersions EP8 and EP9 when matted with TS-100 and cured with excimer
[0230]
[0231]
[0232] Table 12 shows that coatings cured with excimer curing provide very low gloss coatings with good chemical and nail scratch resistance. When matting is achieved with TS-100 and cured under conventional UV curing, the chemical and nail scratch resistance is much worse than when matting and curing with excimer.
[0233] Comparative experiment 10-16
[0234] A representative set of commercially available waterborne UV-curable coating dispersions as specified in Table 13 were applied to Leneta cards (2C Leneta Inc) using a 125 μm wire bar applicator. The coated cards were dried in an oven at 50° C. at an air velocity of 1.2 m / s for 10 minutes. The dried composition thus obtained was subsequently cured using conventional UV atmospheric curing and excimer / UV curing as described above. The measured gloss values are reported in Table 13. The commercially available waterborne UV-curable coating compositions as shown in Table 13 have different compositions from the waterborne radiation-curable coating compositions of the present invention.
[0235] Table 13 : Gloss values of a representative set of commercially available waterborne UV-curable coating compositions after conventional UV curing and combined excimer / UV curing under atmospheric conditions
[0236]
[0237] Table 13 shows that this representative set of commercially available waterborne UV-curable dispersions did not give a matte coating when subjected to excimer / UV curing.
Claims
1. A method for producing a coating from an aqueous radiation-curable coating composition, wherein the method comprises the following steps in the order (1) to (4): (1) applying an aqueous radiation-curable coating composition onto a surface of a substrate, (2) drying the aqueous radiation-curable coating composition to provide an at least partially dried coating composition, (3) irradiating the at least partially dried coating composition with ultraviolet light having a wavelength of ≤220 nm under an inert atmosphere, and then (4) Irradiation with ultraviolet light with a wavelength of ≥300nm or electron beam, The aqueous radiation-curable coating composition is a dispersion comprising: (A) at least one aqueous dispersion of at least one vinyl polymer (A), wherein The polymer system (A) comprises a glass transition temperature T g A vinyl polymer having a temperature of less than or equal to 77°C, wherein T is determined by differential scanning calorimetry as described in the specification g , The polymer system (A) is substantially free of radiation-curable ethylenically unsaturated bonds, and The polymer system (A) has an acid value of 5 to 105 mg KOH / gram (A), (B) at least one radiation-curable diluent (B) having a molar mass of less than 750 g / mol and having an acrylate functionality of 2 to 3, and (C) water and optionally an organic solvent, whereby the optional organic solvent is present in an amount of up to 30% by weight, based on the total amount of water and organic solvent, The amount of (A) is 30 to 75% by weight, and the amount of (B) is 25 to 70% by weight, based on the total amount of (A) and (B).
2. The method according to claim 1, wherein the glass transition temperature T in the polymer system (A) is g The amount of vinyl polymer having a temperature of at most 77°C is at least 55 wt%, more preferably at least 60 wt%, more preferably at least 65 wt%.
3. The method according to any one of the preceding claims, wherein the polymer system (A) comprises at least two T g The difference is at least 20°C, more preferably at least 30°C, more preferably at least 40°C, more preferably at least 50°C, more preferably at least 60°C, preferably at most 200°C, more preferably at most 150°C.
4. The method according to any one of the preceding claims, wherein the polymer system (A) comprises (A1) a carboxylic acid-functional ethylenically unsaturated monomer, and (A2) an ethylenically unsaturated monomer different from (A1).
5. The method according to claim 4, wherein Monomer (A1) is selected from itaconic acid, itaconic anhydride, itaconic acid monoalkyl esters, itaconic acid monoaryl esters, acrylic acid, methacrylic acid, β-carboxyethyl acrylate and combinations thereof, more preferably, monomer (A1) is acrylic acid and / or methacrylic acid, most preferably, monomer (A1) is methacrylic acid; and / or The monomer (A2) is selected from the group consisting of acrylates, methacrylates, arylalkylenes, itaconates and any mixtures thereof.
6. The process according to claim 4 or 5, wherein at least 30% by weight, more preferably at least 50% by weight, even more preferably at least 70% by weight of the total amount of monomers (A2) is selected from methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-octyl acrylate, styrene and mixtures of two or more of said monomers.
7. The method according to any one of the preceding claims, wherein at least 10 wt. %, preferably at least 20 wt. %, more preferably at least 30 wt. %, more preferably at least 40 wt. %, more preferably at least 50 wt. %, more preferably at least 60 wt. %, more preferably at least 70 wt. %, more preferably at least 80 wt. %, more preferably at least 90 wt. %, most preferably 100 wt. % of the radiation curable diluent (B) is selected from: With the corresponding molecular formula C 21 H 32 O8 and its corresponding di(trimethylolpropane) triacrylate (di-TMP3A) with a molar mass of 412 g / mol, di(trimethylolpropane) triacrylate containing an alkoxy group, With the corresponding molecular formula C 21 H 32 O9 and its corresponding glyceryl propoxy triacrylate (GPTA) with a molar mass of 428 g / mol, Glyceryl propoxy triacrylate containing an additional alkoxy group, With the corresponding molecular formula C 14 H 18 O7 and its corresponding pentaerythritol triacrylate (PET3A) with a molar mass of 298 g / mol, Pentaerythritol triacrylate containing an alkoxy group, With the corresponding molecular formula C 15 H 20 O6 and its corresponding trimethylolpropane triacrylate (TMPTA) with a molar mass of 296 g / mol, trimethylolpropane triacrylate containing an alkoxy group, With the corresponding molecular formula C 12 H 18 O5 and its corresponding dipropylene glycol diacrylate (DPGDA) with a molar mass of 242 g / mol, Dipropylene glycol diacrylate containing an additional alkoxy group, and any mixture thereof.
8. The process according to any one of the preceding claims, wherein the at least one radiation-curable diluent (B) has an acrylate functionality of 2.
9. A method according to any one of the preceding claims, wherein The amount of (A) is 35 to 75 wt %, and the amount of (B) is 25 to 65 wt %, preferably, the amount of (A) is 35 to 70 wt %, and the amount of (B) is 30 to 65 wt %; and / or The total amount of (A) and (B) is preferably 10 to 60 wt%, more preferably 15 to 50 wt%, more preferably 15 to 45 wt%, even more preferably 20 to 40 wt%, even more preferably 25 to 35 wt%, based on the total weight of the aqueous radiation curable coating composition.
10. The method according to any one of the preceding claims, wherein the amount of water in the aqueous radiation curable coating composition is at least 30 wt%, or at least 35 wt%, or at least 40 wt%, or at least 45 wt%, or at least 50 wt%, or at least 55 wt%, or at least 60 wt%, or at least 70 wt%, based on the total weight of the aqueous radiation curable coating composition; and / or The amount of optional organic solvent in the aqueous radiation curable coating composition is up to 25 wt. %, preferably up to 20 wt. %, preferably up to 15 wt. %, preferably up to 10 wt. %, more preferably up to 5 wt. %, more preferably up to 5 wt. %, more preferably up to 4 wt. %, more preferably up to 3 wt. %, more preferably up to 2 wt. %, more preferably up to 1 wt. %, wherein the amount of organic solvent is given based on the total amount of water and organic solvent present in the aqueous radiation curable coating composition.
11. The method according to any one of the preceding claims, wherein the polymer system (A) has a radiation-curable ethylenically unsaturated bond concentration of less than 0.50 milliequivalents (meq) / gram (A), more preferably less than 0.40 meq / g (A), more preferably less than 0.30 meq / g (A), more preferably less than 0.20 meq / g (A), more preferably less than 0.10 meq / g (A).
12. The method according to any one of the preceding claims, wherein the polymer system (A) has a weight average molecular weight M of at least 5,000 g / mol, more preferably at least 10,000 g / mol, even more preferably at least 20,000 g / mol, even more preferably at least 30,000 g / mol, and preferably at most 1,000,000 g / mol, more preferably at most 500,000 g / mol, even more preferably at most 250,000 g / mol. w , wherein the weight average molecular weight M w Assayed as described in the instructions.
13. The method according to any one of the preceding claims, wherein the dispersion consisting of (A), (B) and (C) has a z-average particle size of 20 to 1000 nm, preferably 25 to 500 nm, more preferably 25 to 250 nm, most preferably 30 to 200 nm, whereby the z-average particle size is determined by the method as described in the description.
14. The method according to any one of the preceding claims, wherein the irradiation in step (3) is carried out by an excimer UV lamp, preferably with UV light having a wavelength ≥120 nm, more preferably ≥150 nm, particularly preferably 172 nm or 195 nm.
15. The method according to any one of the preceding claims, wherein UV radiation is applied in step (4) and the aqueous radiation curable coating composition comprises one or more photoinitiators.
16. An aqueous radiation curable coating composition according to any one of claims 1 to 13.
17. A coated substrate, wherein the coated substrate is obtained by the method according to any one of claims 1 to 15.
Citation Information
Patent Citations
Acylphosphine oxide compounds
US4324744A
Bisacylphosphine oxides, the preparation and use thereof
US4737593A
Daylight curing compositions containing bisacylphosphine oxide photoinitiators
US5534559A
Molecular complex compounds of acylphosphine oxide and alpha -hydroxy ketones as photoinitiators
US5942290A
Alkylphenylbisacylphosphine oxides and photoinitiator mixtures
US6020528A